Política Externa Para La Integración Fronteriza A Partir Del Caso De La Triple Frontera Brasil, Colombia Y Perú En Los Gobiernos De Lula, Uribe Y García (2006-2011) - Londoño Niño, Edgar Andrés [UNESP] (My University, 2015)
This article refers to some of the elements of border foreign policy under Lula (2006-2011), Uribe (2006-2010) and Garcia (2006-2011) based on domestic factors, foreign policy guidelines and bilateral relations with neighbors around the case of the Triple Border between Brazil, Colombia and Peru. This article notes that during this period, Brazil gave more attention to the Triple Border than its neighbors, in accordance with foreign policy orientation for both the region and the Amazon. Peru consolidated its economic interest in its Amazon region without focusing attention on the border region studied herein. Colombia focused on the fight against internal guerrilla and the defense of its security policy. This paper shows how foreign policy is essential to analyzing the limits and possibilities of border integration processes.
Foreign policy for border integration in the case of the triple border between Brazil, Colombia and Peru under the governments of Lula, Uribe and Garcia (2006-2011)
Keywords: Foreign policy; Garcia; Lula; Triple border; Uribe